Implementation of the Scanning Laser Doppler Vibrometer Combined with a Light-Weight Pneumatic Artificial Muscle Actuator for the Modal Analysis of a Civil Structure - K. Deckers; P. Guillaume; C. Vuye; D. Lefeber (Shock and Vibration)
The identification of the modal parameters of bridges and other large civil constructions has become an important research issue. Different approaches have been proposed depending on the excitation used: ambient excitations (due to wind, traffic, …) or artificial excitations (e.g. impact test with heavy drop weights). In practice it turns out that not all modes are well excited by the ambient forces. Hence the application of an artificial actuator is advisable. The problem is that larger constructions often require large and heavy excitation devices, which are hard to manipulate. Another difficulty encountered in performing a modal analysis on large civil constructions is the necessity for a large number of high sensitivity sensors. Consequently a large number of cables has to be installed resulting in a large setup time.